THE LEGAL (IN)SECURITY IN THE VIRTUAL ENVIRONMENT: ASPECTS REGARDING THE REGULATION OF THE ACTIVITY OF DIGITAL INFLUENCERS (REMUNOM, 2024)
The growth of consumer relationships within the virtual environment revealed the emergence of a new figure in the relationship, digital influencers. Such figures have great relevance in social networks, given the large number of followers available. However, the activity carried out is not regulated in the Brazilian territory, making it relevant to address the implications brought by consumer relations and the role of the State as a guarantor of the legal security of consumers. In light of this scenario, this article sought, based on bibliographical research and the deductive method covered by analyses of the Consumer Protection Code and the Civil Code, data analysis, and jurisprudence, to find legal (in)security in the virtual environment and the importance found in the regularization of the activity of digital influencers.